2015
DOI: 10.1080/21645515.2015.1057671
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of the impact of pneumococcal conjugate vaccines in developing countries

Abstract: Infection due to Streptococcus pneumoniae is a leading cause of morbidity and mortality in young children, especially in developing countries. With the support of Gavi, the Vaccine Alliance, the majority of these countries have introduced pneumococcal conjugate vaccines (PCV) into their national immunization programs and early data demonstrate a high degree of effectiveness, translating to enormous public health benefit through both direct and indirect (herd) effects. Future vaccination strategy may be focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 10 publications
3
34
0
Order By: Relevance
“…Our predictions are in line with the experience of PCV7 in Europe and North America [37-44], as well with post-PCV trends observed in the few studies from low-income settings [36]. In the region of Kilifi in Kenya, where a catch-up campaign was conducted at PCV introduction, impact studies have shown a two third reduction in VT carriage prevalence across all age groups within two years of PCV10 introduction with a catch-up campaign among children <5 years [43].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our predictions are in line with the experience of PCV7 in Europe and North America [37-44], as well with post-PCV trends observed in the few studies from low-income settings [36]. In the region of Kilifi in Kenya, where a catch-up campaign was conducted at PCV introduction, impact studies have shown a two third reduction in VT carriage prevalence across all age groups within two years of PCV10 introduction with a catch-up campaign among children <5 years [43].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, we were not able to assess the impact of PCV on pneumococcal pneumonia, the burden of which is much higher than that of IPD [34], given the lack of robust data and the challenges in the aetiological assessment of clinical pneumonia. Results from ongoing studies in Gavi-eligible countries [35, 36] might help modelling work on the impact of PCV on pneumonia in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CAP due to serotypes included in the PCV7 declined by 88% (IRR 0.12, 95% CI 0.08–0.20; p < 0.001), and CAP due to the additional 6 serotypes in PCV13 declined by 30% (IRR 0.70, 95% CI 0.51–0.96; p = 0.024). This study and other previous studies described the finding of so-called herd immunity, reducing the incidence of pneumococcal pneumonia in children and adults, after the introduction of PCV7 and PCV13 into the infant immunization programs [ 29 , 30 ]. Other authors found that although PCV13 protects against key serotypes that increased after routine immunization with the PCV7, its potential for herd immunity and serotype replacement is uncertain [ 31 37 ].…”
Section: Discussionsupporting
confidence: 53%
“…15 Pneumococcal conjugate vaccines have been effective in reducing pneumococcal disease both directly, by protecting individual children, and indirectly, by preventing transmission of disease-causing serotypes to susceptible unimmunised people. 2,17 Vaccines have targeted the most high-burden pathogens but some causes of pneumonia are not preventable by use of vaccines. Pathogens not preventable by vaccines include non-vaccine-type S pneumoniae, Staphylococcus aureus, Salmonella, Klebsiella pneumoniae, Mycoplasma pneumoniae, Chlamydophila pneumoniae, Mycobacterium tuberculosis, and viruses other than influenza, such as respiratory syncytial virus, parainfluenza viruses 1-3, human metapneumovirus, adenovirus, coronavirus, and bocavirus.…”
Section: Aetiology and Vaccine Coveragementioning
confidence: 99%